A means of illustrating horticulture - Chandler, Clarence Asa (My University, 1900)
Introduction: The act of Congress, which gave land to each state for the endowment, support and maintenance of a school where the leading object should be to teach such branches of learning as are related to agriculture and the mechanic arts, virtually established an agricultural college in each state. Horticulture is one of the branches which goes largely to make up agriculture, and it should be the object of such colleges to provide instruction such that those students who wish to become proficient as horticulturists should be given an opportunity to do so. I know of no such place at the present time where a person can go and learn commercial fruit growing, so that he will be competent to take charge of a place, either for himself or some one else without the costly experience all successful fruit growers have had to pass through. Such information, when gotten only by experience, paid for by himself, is costly, for it often takes years of cultivation and patience as well as money before one can find out that a certain variety is of no value as a money maker. In most of the Agricultural colleges, the present equipment seems to be inadequate for such teaching. But if a thorough course of practical scientific work could be provided, after its completion one would be ready to go into the practical vocation of growing fruit. If the farmer of this state were taught how to grow their own fruit, many thousands of dollars annually, which now go to California or other fruit growing states would be saved, besides getting a better article making home more attractive and improving things in general.
Citation: Chandler, Clarence Asa. A means of illustrating horticulture. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Horticulture; Fruit; Agricultural Colleges; Theses